2010
DOI: 10.1021/jp105767y
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Photochemistry at Low Temperatures and Spectroscopic Properties of γ-Butyrothiolactone

Abstract: The five-membered heterocyclic gamma-butyrothiolactone was isolated in a low-temperature, inert Ar matrix, and the UV-visible (200 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 50 publications
8
20
0
Order By: Relevance
“…Several reports have pointed out that the strain energies of cyclic molecules are influenced by heteroatom substitution or functionalization. 32 35 Thus, our results are comparable to these reports. The influence of substitution with the halogen atoms is quite minimal when compared to the heteroatom effect on the CHP ring.…”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several reports have pointed out that the strain energies of cyclic molecules are influenced by heteroatom substitution or functionalization. 32 35 Thus, our results are comparable to these reports. The influence of substitution with the halogen atoms is quite minimal when compared to the heteroatom effect on the CHP ring.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Most theoretical methods often require the computation of the total energies of the molecule of interest relative to an acyclic strain-free counterpart. The strain energies of the studied systems have been computed at the MP2/aug-cc-pVTZ and the M06-2X/6-311++G(d,p) level of theory in line with refs ( 21 , 32 ). This approach involves the computation of the ring strain energy relative to the strain energy of the six-membered counterparts, which several studies had reported to be less strained among the cycloalkane family.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Regarding cyclic thioesters, i.e., thiolactones, small and medium-sized thiolactones (4 < n < 7), such as β-propiolactone (n = 4), 153 γ-butyrothiolactone (n = 5), 154 and δvalerothiolactone (n = 6) 155 are constrained in the less favorable anti conformation (Figure 9). Computational analysis suggests that this is also the case for ε-caprothiolactone (n = 7).…”
Section: Peptide Thioesters and Peptide Selenoesters: General Propert...mentioning
confidence: 99%
“…Ethylketene is evidenced by bands in the FTIR spectrum at 1141 cm −1 (Figure 3), 2135 cm −1 , and 2130 cm −1 (Figure 2), matching bands observed for matrix-isolated ethylketene in the literature. 25 There is also a tiny feature at m/z = 70 (CH 3 CH 2 CH=C=O + ) observable in the mass spectrum following 1000 K pyrolysis. The coproduct of elimination, H 2 (IE = 15.4 eV), 18 cannot be observed in the mass spectra.…”
Section: B Products Of Eliminationmentioning
confidence: 99%